Modification of Cellulose Acetate Films Using Nanofillers Based on Organoclays - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (Elsevier Ltd, 2012)
The present work has been oriented on the development of cellulose acetate films with nanofillers of montmorillonite/alkylammonium (hexa- and tetra-decyltrimethylammonium) and montmorillonite/ chitosan which have been synthesized using a cationic exchange process. All synthesized organoclays have been characterized using X-ray diffraction (XRD), thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FTIR). These analyses confirmed the modification of clay structures which proved to be dependent on the chemical structure of chosen organic precursor. On the other hand, the different organoclays have been used to produce cellulose acetate nanocomposites by solvent-casting technique. The nanocomposite films have been characterized by XRD, TGA, Differential scanning calorimetry (DSC), oxygen and water vapor permeability and scanning electronic microscopy (SEM). All nanocomposites obtained showed the intercalation of polymer inside the clay structure and an important reduction of oxygen transmission rate (OTR) compared to cellulose acetate films without nanofillers. © 2011 Elsevier Ltd. All rights reserved.